The Brazilian School Principals - Ângelo Ricardo de Souza (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This article discusses the policy nature of school principal, considering the thoughts of many authors about school administration and the debate about politics, power and burocracy. The study still presents a profile of Brazilian school principals with the data of Basic Education Evaluation System - SAEB, of 2003, specially comparing elements about gender, experience and formation of school principals, and aspects linked with methodology to provide/indicate the school principal and its possible democratic vocation.